High-energy lithium-ion hybrid supercapacitors composed of hierarchical urchin-like WO3/C anodes and MOF-derived polyhedral hollow carbon cathodes. Issue 37 (12th September 2016) - Xu, Juan; Li, Yuanyuan; Wang, Lei; Cai, Qifa; Li, Qingwei; Gao, Biao; Zhang, Xuming; Huo, Kaifu; Chu, Paul K.
Abstract : High-energy lithium-ion hybrid supercapacitors composed of hierarchical urchin-like WO3 /C anodes and MOF-derived polyhedral hollow carbon cathodes were designed and fabricated. Abstract : A lithium-ion hybrid supercapacitor (Li-HSC) comprising a Li-ion battery type anode and an electrochemical double layer capacitance (EDLC) type cathode has attracted much interest because it accomplishes a large energy density without compromising the power density. In this work, hierarchical carbon coated WO3 (WO3 /C) with a unique mesoporous structure and metal–organic framework derived nitrogen-doped carbon hollow polyhedra (MOF-NC) are prepared and adopted as the anode and the cathode for Li-HSCs. The hierarchical mesoporous WO3 /C microspheres assembled by radially oriented WO3 /C nanorods along the (001) plane enable effective Li + insertion, thus exhibit high capacity, excellent rate performance and a long cycling life due to their high Li + conductivity, electronic conductivity and structural robustness. The WO3 /C structure shows a reversible specific capacity of 508 mA h g −1 at a 0.1 C rate (1 C = 696 mA h g −1 ) after 160 discharging–charging cycles with excellent rate capability. The MOF-NC achieved the specific capacity of 269.9 F g −1 at a current density of 0.2 A g −1 . At a high current density of 6 A g −1, 92.4% of the initial capacity could be retained after 2000 discharging–charging cycles, suggesting excellent cycle stability. The Li-HSC comprising a WO3 /C anode and a MOF-NC cathode boasts a large energy density of 159.97 W h kg −1 at a power density of 173.6 W kg −1 and 88.3% of the capacity is retained at a current density of 5 A g −1 after 3000 charging-discharging cycles, which are better than those previously reported for Li-HSCs. The high energy and power densities of the Li-HSCs of WO3 /C//MOF-NC render large potential in energy storage.